2010
DOI: 10.1016/j.febslet.2010.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into eukaryotic aquaporin regulation

Abstract: a b s t r a c tAquaporin-mediated water transport across cellular membranes is an ancient, ubiquitous mechanism within cell biology. This family of integral membrane proteins includes both water selective pores (aquaporins) and transport facilitators of other small molecules such as glycerol and urea (aquaglyceroporins). Eukaryotic aquaporins are frequently regulated post-translationally by gating, whereby the rate of flux through the channel is controlled, or by trafficking, whereby aquaporins are shuttled fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 94 publications
(202 reference statements)
4
123
0
Order By: Relevance
“…For the case of AQY1, its crystal structure revealed that the water channel was regulated by gating (45), and it was suggested that reconstitution of AQY1 into proteoliposomes, which have a FIGURE 4. CD spectra and melting curves, demonstrating the stability of hAQP10.…”
Section: Discussionmentioning
confidence: 99%
“…For the case of AQY1, its crystal structure revealed that the water channel was regulated by gating (45), and it was suggested that reconstitution of AQY1 into proteoliposomes, which have a FIGURE 4. CD spectra and melting curves, demonstrating the stability of hAQP10.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the fact that ovaries from water-stressed specimens started basal oocyte resorption 48h after water deprivation, no significant differences were observed in the levels of BgAQP mRNA in the ovary between control and water-stressed specimens. AQPs are regulated post-translationally by phosphorylation-dependent gating and especially by trafficking of the protein between the plasma membrane and the intracellular storage vesicle (Törnroth-Horsefield et al, 2010); thus, the effects of water stress on BgAQP may not be evident at the mRNA level.…”
Section: A Herraiz and Othersmentioning
confidence: 99%
“…In the cell membrane, each AQP is folded into a right-handed -barrel, with a central transmembrane channel surrounded by the six full-length transmembrane helices and the two NPA-containing loops, B and E. This conformation in the plasma membrane is known as the hourglass model (Jung et al, 1994). Some AQPs, known as aquaglyceroporins, transport other non-charged solutes such as glycerol and urea in addition to water (Gomes et al, 2009;Rojek et al, 2008;Törnroth-Horsefield et al, 2010). The amino acids forming the ar/R constriction (His is replaced by the smaller amino acid Gly in aquaglyceroporins) (Beitz et al, 2006), and five other residues (P1-P5) located on the side-chains neighbouring the ar/R constriction (Froger et al, 1998), are responsible for substrate selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their wellestablished water-and glycerol-transporting functions, AQPs have also been proposed to transport other small molecules and gases, including carbon dioxide, ammonia, nitric oxide and hydrogen peroxide (Musa-Aziz et al, 2009;Miller et al, 2010;Wang and Tajkhorshid, 2010). Although some gases are theoretically small enough to pass through the aqueous pore of the AQP, compelling evidence is lacking for physiologically relevant gas transport, partly because the intrinsic lipid-mediated membrane permeability to most gases is high (Yang et al, 2000;Missner et al, 2008;Tornroth-Horsefield et al, 2010). Current evidence suggests that most, if not all, significant biological functions of the mammalian AQPs, including those described here, can be attributed to AQPfacilitated water and/or glycerol transport.…”
Section: Aqp Structure Function and Regulationmentioning
confidence: 99%